Humanistic Approaches to Medical Practice - Ioan, Beatrice Gabriela; Iorga, Magdalena (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Medical practice is a mixture of science and art, technique and humanism. The importance of human beings is more obvious in medicine than in any other field. At the center of medical care is the patient, and at its base and that of the entire medical system is the relationship that is established between the patient and the medical staff. Overspecialization is a big component of modern medicine, with professionals working in increasingly narrow fields, which makes patients routinely treated by multidisciplinary teams. This draws attention to the importance of appropriate relationships between members of the medical team for the success of the therapeutic approach. In the context of technological progress in medicine, the need to relate to the humanistic values of the medical profession and the complexity of the medical act in which technical aspects are intertwined with cultural, ethical, legal, psychological, and sociological issues becomes increasingly clear. This Special Issue is dedicated to the humanistic values of medical practice. It includes articles that approach various aspects of the so-called humanistic medicine, drawing a picture of what contemporary medicine should strive for.